GANRA-5 protects mice from X-ray irradiation-induced dysfunction of the immune system. (August 2014) - Liu, T.; Pei, H.; Xu, D.; Zhang, Y.; Wan, J.; Wu, X.; Zhang, X.; Sun, F.; He, J.; Li, P.; Tian, N.; Wang, J.; et al.
Abstract Ionizing radiation produces reactive oxygen species (ROS), which cause damage to cells. We have synthesized a class of ROS scavengers and found that one of them, named GANRA-5, exhibits high radio-protective effects against both heavy ion irradiation and X-rays, while at the same time displaying low levels of toxicity. Pre-administration with an effective dose of GANRA-5 reduces radiation-induced damage to tissues and increases the survival rate of exposed mice. In this study, we evaluated the changes to the immune system via X-ray irradiation, and investigated how pre-administration of GANRA-5 exhibited preventative characteristics. Compared to the irradiated control groups, GANRA-5 treatment significantly reduced the radiation-induced spleen shrinkage and pathological changes. Moreover, pretreatment with GANRA-5 significantly (p < 0.01) enhanced the cellular immune response, which was characterized by higher peritoneal macrophage as well as splenocyte survival, and a higher ratio of CD4+/CD8+ T lymphocytes. In addition, GANRA-5 treatment before whole body irradiation significantly improved the humoral response (p < 0.01) as indicated by the higher antibody titers of IgG, IgA, and IgM. Furthermore, GANRA-5 treatment significantly (p < 0.01) countered radiation-induced decreases in the titers of serum IL-2 and IL-4 when compared to irradiated but untreated control groups. In summary, these findings indicate that GANRA-5 provides effective protection to the immune system against X-ray-induced immunosuppression.